Preparing Students for Success in Hybrid Learning Environments with Academic Resource Centers. (March 2017) - Newman, Daniel; Dickinson, Michael
Abstract : This chapter describes institutional and andragogical best practices for preparing students to succeed in hybrid courses through the programming of academic resource centers, offers information on how to create peer support systems for students, and outlines some of the common pitfalls for students encountering a hybrid course for the first time.